"Our teachers and the limits of cognition": Dietzgen and the challenge of McLaren's epistemology. (June 2017) - Boxley, Simon
In Peter McLaren's words "We need a philosophically grounded alternative to capitalism", but what does such a philosophical grounding look like? Need it be shared? The philosophical basis for practice was not shared by Lenin and Bogdanov, for example, and yet both retained the ability to work together in the Bolshevik party. There's a profound difference between god-building, and god-seeking . Socialists have strong traditions of both. Peter McLaren's recent work fits into the latter category. I will engage with this project, because I think Peter's position, whilst honourable, lacks the visionary power of the former. And to these I would like to add a third position, one which seeks to extend to all of the material universe and to all living things a sacred character, but without any requirement for categories such as god. There are of course many mystic traditions which espouse something similar, but relatively few socialists have developed politically this position, as espoused by the tanner-philosopher Josef Dietzgen (though there are certainly close links between Dietzgenism and god-building). My argument for raising such seemingly arcane concerns, is rather similar to that of Lenin whose immersion in philosophy in writing Materialism and Empirio-Criticism primarily met the political requirements of the day. Amidst ubiquitous talk of the Anthropocene, and a sudden rise in interest in Bogdanov on the Marxist left, now is the moment to look to the prospect of taking up a Bogdanovite project, not to build a new god, but to re-sacralise nature. In this paper, I begin to mobilise an unlikely alliance around this vision: not only Dietzgen, but deep ecologists and even Jiddu Krishnamurti assist in exploring the limitations of McLaren's position.